PENGARUH KINERJA ORGANISASI TERHADAP KUALITAS PELAYANAN PUBLIK DI DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN KARAWANG - Yana, Neneng Rizki; Aryani, Lina; Putri, Lolita Deby Mahendra (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
This study was motivated by issues surrounding organizational performance and the quality of public services at the Karawang Regency Education, Youth and Sports Agency. Therefore, the purpose of this study is to determine the effect of organizational performance on the quality of public services at the Karawang Regency Education, Youth and Sports Agency. This study This research employs a quantitative approach with correlation analysis. The population in this study consists of employees and service applicants at the Education, Youth, and Sports Office of Karawang Regency. The theory used to analyse this research is the organizational performance theory by Dwiyanto, which consists of productivity, service quality, responsiveness, responsibility, accountability, and Zeithaml's public service quality theory, which consists of tangibles, reliability, responsibility, assurance, and empathy. Before conducting data analysis, the research instrument was tested, consisting of validity and reliability tests. Data analysis was conducted using IBM SPSS 25. Data analysis consisted of normality tests, heteroscedasticity, linearity, correlation tests, determination tests and simple linear regression testing. The results of this study indicate a significant influence of organizational performance on the quality of public services at the Karawang Regency Education, Youth, and Sports Office. This is evidenced by the calculated t-value > t table (20.537 > 1.987) and significance value (0.000<0.05). Then, from the determination calculation, a value of 81.1% was obtained, which means that the influence of organizational performance on the quality of public services at the Karawang Regency Education, Youth and Sports Agency is very strong and significant. Then, from the determination calculation, a value of 81.1% was obtained, which means that the influence of organizational performance on the quality of public services at the Karawang Regency Education, Youth and Sports Agency is very strong and significant